2003
DOI: 10.3189/172756503781830377
|View full text |Cite
|
Sign up to set email alerts
|

New velocity map and mass-balance estimate of Mertz Glacier, East Antarctica, derived from Landsat sequential imagery

Abstract: Automatic feature tracking on two Landsat images (acquired inJanuary 2000 and December 2001) generates a complete and accurate velocity field of Mertz Glacier, East Antarctica. This velocity field shows two main tributaries to the ice stream. Between the tributaries, a likely obstruction feature in the bedrock results in a slow-down of the flow. A third Landsat image, acquired in 1989 and combined with the 2000 image, permits the determination of the glacier mean velocity during the 1990s. Although some parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 38 publications
1
44
0
1
Order By: Relevance
“…The ice sheet mass balance can only be computed thanks to this technique if the snow accumulation rate is well known over the drainage basin. For instance, it has been suggested that the discharge flux over the Mertz basin was too low to compensate for the snow supply through accumulation (lower than the accumulation rate) so that this sector may be in a positive imbalance [93]. However, the authors also pointed out that large errors in the accumulation maps impede reaching a firm conclusion about the Mertz mass balance [93].…”
Section: Balance Velocity and Ice Dynamicsmentioning
confidence: 94%
See 1 more Smart Citation
“…The ice sheet mass balance can only be computed thanks to this technique if the snow accumulation rate is well known over the drainage basin. For instance, it has been suggested that the discharge flux over the Mertz basin was too low to compensate for the snow supply through accumulation (lower than the accumulation rate) so that this sector may be in a positive imbalance [93]. However, the authors also pointed out that large errors in the accumulation maps impede reaching a firm conclusion about the Mertz mass balance [93].…”
Section: Balance Velocity and Ice Dynamicsmentioning
confidence: 94%
“…For instance, it has been suggested that the discharge flux over the Mertz basin was too low to compensate for the snow supply through accumulation (lower than the accumulation rate) so that this sector may be in a positive imbalance [93]. However, the authors also pointed out that large errors in the accumulation maps impede reaching a firm conclusion about the Mertz mass balance [93]. Similarly, Fricker et al [94] showed that for the Lambert Glacier and Amery ice shelf system the poor knowledge of accumulation rate over the drainage basin prevents from applying such a technique.…”
Section: Balance Velocity and Ice Dynamicsmentioning
confidence: 99%
“…Similar to the ASTER images, the co-registration of the Landsat images is a key step to measure glacier surface velocity fields which strongly affects the accuracy of the obtained velocities [24,33]. For this purpose, we used an automated precise registration and orthorectification package, called AROP, to obtain a set of precisely co-registered images [34].…”
Section: Landsat Imagerymentioning
confidence: 99%
“…Many authors have made estimates of the mass balance of the entire ice sheet [1][2][3][4][5][6] as well as individual drainage systems [7,8] . The fourth assessment report of the Intergovernmental Panel on Climate Change suggests that mass losses from Antarctic Ice Sheet have likely contributed to sea level rise over the past 30 years, the assessment uncertainty, however, is still very large 1) , studies on Antarctic Ice Sheet mass balance are increasingly of importance and necessity in context of the global warming [9] .…”
Section: Introductionmentioning
confidence: 99%